Assessment of miRNA expression profile and differential expression pattern of target genes in cold-tolerant and cold-sensitive tomato cultivars - Koc, Ibrahim; Filiz, Ertugrul; Tombuloglu, Huseyin (Taylor & Francis Ltd, 2015)
MircroRNAs (miRNAs) are small non-coding RNAs about 21 nt in length. These short transcripts regulate developmental and stress responses in plants. Cold stress is one of the most restraining abiotic factors adversely affecting the plant yield. In the present study, some cold stress-related miRNAs (miR167, miR169, miR172, miR393 and miR397) in tomato (Solanum lycopersicum) were assessed at early time points (0, 1, 4 and 16 h) of cold exposure. Relative expression of miRNAs was measured by stem-loop quantitative reverse transcription polymerase chain reaction. The results showed that miR167, miR169, miR172 and miR393 were activated in the early time points of cold treatment. Especially, miR172 was found to have highest expression level. Furthermore, target genes of selected miRNAs were identified and their expression profiles were assessed between cold-sensitive and cold-tolerant cultivars of tomato. It was found that inferred expression patterns of target genes were differentiated between the cultivars. Analysis of cis-acting elements showed that miRNAs had stress-responsive elements. Meanwhile, since no miR393 sequence is available, putative miR393 sequence and its secondary structure were predicted in tomato. These results may provide a framework for further analysis in terms of understanding the response of miRNAs against cold stress in tomato.
Keywords: cold stress; miRNA; stem-loop qRT-PCR; tomato; cis-acting element; target genes